The Effect of Students Learning Style and Perceptions of the Teachers Teaching Styles Variants on Learning Outcomes in Sekolah Penggerak - Eka Hendi Andriansyah; Achmad Adi Kurniawan (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
Based on preliminary observations made by researchers at the three locations of SMAN which have the status of driving schools in Gresik Regency, it shows that there are problems in the economics learning outcomes on national income material in class XI. This information can be seen in the values of TP 2 in the national income material for several students who scored under the Minimum Completeness Criteria (KKM), where there is a minimum score of 75. This study aims to analyze the joint effect of kinesthetic learning styles and student perceptions regarding the variance of the interactional teacher's teaching style on the learning outcomes of students on national income material in driving schools. The population of 3 SMANs with the status of driving schools in Gresik Regency was 432 and then a simple random sampling technique was carried out. The sample used in this study were 144 students using explanatory quantitative methods and using tests, hypotheses, classical assumptions, multiple linear regression analysis. Based on the results of data processing, the coefficient of determination (R-squared) is 0.94. Thus, it can be concluded that the combined influence of variables X1 and X2 on variable Y is 94%, while 6% is caused by the influence of other variables. Thus it is expected that schools will pay attention to each student's learning style and conduct teacher training to improve the ability of teachers to teach variations so that student learning outcomes are optimal